EXPERIMENTAL CRYSTALLIZATION OF A HIGH-K ARC BASALT: THE GOLDEN PUMICE, STROMBOLI VOLCANO (ITALY) - Di carlo I.; Pichavant M.; Rotolo S.G.; Scaillet B. (My University, 2006)
The near-liquidus crystallization of a high-K basalt (PST-9 golden pumice, 49·4 wt % SiO2, 1·85 wt % K2O, 7·96 wt % MgO) from the present-day activity of Stromboli (Aeolian Islands, Italy) has been experimentally investigated between 1050 and 1175°C, at pressures from 50 to 400?MPa, for melt H2O concentrations between 1·2 and 5·5 wt % and ?NNO ranging from ?0·07 to +2·32. A drop-quench device was systematically used. AuPd alloys were used as containers in most cases, resulting in an average Fe loss of 13% for the 34 charges studied. Major crystallizing phases include clinopyroxene, olivine and plagioclase. Fe–Ti oxide was encountered in a few charges. Clinopyroxene is the liquidus phase at 400?MPa down to at least 200?MPa, followed by olivine and plagioclase. The compositions of all major phases and glass vary systematically with the proportion of crystals. Ca in clinopyroxene sensitively depends on the H2O concentration of the coexisting melt, and clinopyroxene Mg-number shows a weak negative correlation with ?NNO. The experimental data allow the liquidus surface of PST-9 to be defined. When used in combination with melt inclusion data, a consistent set of pre-eruptive pressures (100–270?MPa), temperatures (1140–1160°C) and melt H2O concentrations is obtained. Near-liquidus phase equilibria and clinopyroxene Ca contents require melt H2O concentrations <2·7–3·6 and 3 ± 1 wt %, respectively, overlapping with the maximum frequency of glass inclusion data (2·5–2·7 wt % H2O). For olivine to crystallize close to the liquidus, pressures close to 200?MPa are needed. Redox conditions around ?NNO = +0·5 are inferred from clinopyroxene compositions. The determined pre-eruptive parameters refer to the storage region of golden pumice melts, which is located at a depth of around 7·5?km, within the metamorphic arc crust. Golden pumice melts ascending from their storage zone along an adiabat will not experience crystallization on their way to the surface.
Keywords: basalt; pumice; experiment; phase equilibria; Stromboli